THE INFLUENCE OF HUMAN RESOURCE DEVELOPMENT ON THE WORK PRODUCTIVITY OF GOVERNMENT APPARATUS IN BANDUNG CITY - Ade Mubarok (CV. Radja Publika, 2022)
Human Resource Development (HRD) is an essential factor in improving employee performance and organizational effectiveness, particularly within public sector institutions. This study aims to analyze the influence of Human Resource Development on the work productivity of government apparatus in Bandung City. The research employed a quantitative approach using a descriptive and associative research design. Data were collected through questionnaires distributed to government employees working in several regional government institutions in Bandung City. The collected data were analyzed using descriptive statistics and simple linear regression analysis with the assistance of SPSS software. The findings revealed that Human Resource Development has a positive and significant influence on employee work productivity. HRD programs such as education and training, competency improvement, career development, and skill enhancement contributed positively to employees’ effectiveness, efficiency, discipline, and overall performance. The study also identified several challenges in the implementation of HRD programs, including unequal access to training opportunities and administrative constraints. Nevertheless, effective HRD implementation was proven to improve employee competencies and support better public service delivery. Therefore, the Bandung City Government is encouraged to strengthen HRD policies and expand competency development programs to improve organizational productivity and public service quality.